Sosialiasai Sosialisasi Keterampilan Mediasi pada Mahasiswa Universitas Mataram untuk Membentuk Generasi Muda Damai - uwi, uwimaratayadi; Dyah Indraswati (PT. Karya Inovatif Nusantara, 2025)
In the era of globalization and modernization that is increasingly complex, conflicts and disputes have become an inseparable part of human life. Humans as social beings depend on other humans and their environment. Interaction is an inseparable part of human life. However, in the dynamics of interaction, both between individuals, groups, and countries, conflicting interests often arise, leading to conflict. This PKM aims to: (1) increase the awareness of University of Mataram students about the importance of mediation skills (2) develop the mediation skills of University of Mataram students to be able to become agents of change in the campus environment and the general public (3) form a young generation who are able to resolve conflicts peacefully and build a more harmonious society. This PKM was carried out in the form of socialization using the lecture and question and answer method. The results of this PKM activity are in the form of: (1) increasing students' awareness of the concept and practice of mediation to form a generation of peace in the midst of the campus community and the general public (2) students acquire mediation skills that are useful for themselves when entering the world of work and are able to facilitate negotiations between various parties. (3) Students become more open, tolerant, and empathetic to differences of opinion.